Application of the French Pattern Construction System to the ‘Artheia’ Evening Gown Goddess Theme - Nur Hidayah, Erika Wahyu; Kusumastuti, Adhi (Universitas Negeri Semarang, 2025)
Evening gowns are costume made piece that require precise pattern construction to achieve an elegant, proportional, and aesthetically appealing form. This study aimed to describe the application of the French pattern system in creating the evening gown “Artheia” with the theme Goddess and to assess its feasibility through expert judgment. This practice-based research was conducted over four mounts, covering the stages of exploration, design, realization, and evaluation. This French pattern system was applied to the bustier and mermaid silhouette to ensure accurate fit, stable structure, and proportionality. Evaluation by three experts’ judgement was conducted on six indicators, design (93.33%), size (86%), sewing technique (77%), aesthetics (88%), performance (89%), and distinctiveness (93%), with the majority of indicators classified as very feasible. The results indicated that the “Artheia” gown meets professional quality standards. Based on study, it can be concluded that the French patternmaking system was effective in producing couture style evening gown and could serve as reliable method for pattern construction in both the fashion industry and fashion education.